My boss is an app and it exploits me: precarious subjectivities among on-demand delivery couriers and drivers - Bedoya Dorado, Cristian; Maca Urbano, Deidi (Revista Colombiana de Ciencias Sociales, 2025)
The uberization of work constitutes a new mode of labor organization within the broader framework of capitalist accumulation, a context in which subjectivities are continually produced and reproduced. This article examines the repertoires that shape the subjectivation process of workers who generate income through mobile applications (apps) offering delivery and transportation services in the city of Santiago de Cali (Colombia). A qualitative empirical study was conducted with 24 participants, using semi-structured interviews. The results were examined through a Critical Discourse Analysis (CDA) and discussed in light of contributions from the Social Studies of Work and Critical Management Studies. The findings indicate that, under precarious working conditions associated with vulnerability and exposure to danger inherent to their tasks—and in the absence of social protection—participants position themselves through different worker labels and incorporate a discourse of freedom and autonomy tied to the flexibility offered by app-based work. This discourse coexists with a form of “self-exploitation” shaped by a subordinated relationship with the apps and their algorithms.